Paidéia divina: formação e destinação do homem em Joseph de Maistre - Verçosa Filho, Élcio de Gusmão (2008)
The scope of this study is the examination of the theology of history of the Savoyard writer Joseph-Marie de Maistre (1753-1821) from the perspective of the concept of Paideia or divine education developed in a branch of providential thinking that used to be predominant in the theology of early Eastern Christianity, especially in the works of Origen. The core argument is the claim that this perspective may prove to be particularly able to provide the necessary grounds for a global interpretation of his thought, harmonizing and integrating the diversity of aspects society, politics, anthropology, theory of knowledge by which it is characterized, and offering a privileged view on the historical formation of Man that is constantly referred to his eschatological destiny. My contention is that this is so because Joseph de Maistre is essentially a religious thinker of man and history, in spite of what his strong concerns for political issues, quite invariably brought to the limelight, might have led many commentators to believe. Thus, the study s primary aim is to put forward a picture of his doctrine and its importance in the history of ideas of a kind that was seldom attempted, a reading of the whole Maistre grounded on the Christian idea of a providential education of Mankind (or of a pedagogical divine Providence) which has as its immediate end (and that is Maistre s personal contribution to this long tradition) the bringing up of concrete men and women within the open finitude of their social environment and, eventually, as its final aim, the annihilation of evil in the universe through the acceptance of suffering and evil and their transfiguration in the imitation of Christ, the ultimate model of perfection for the human being